ChemInform Abstract: Design, Synthesis and Characterization of RXFP1‐Selective Human Relaxin Analogues. Issue 33 (August 2015) - Chan, Linda J.; Hossain, Mohammed A.; Separovic, Frances; Samuel, Chrishan S.; Wade, John D.
Abstract Review: 9 refs.